A Tightrope with a Net - Monacelli, Claudia (Meta, 2004)
AbstractThis is a small-scale, corpus-based study on the effects of lexical repetition, as a cohesive device, on textual coherence. Following Hoey’s work on patterns of lexis (1991), we introduce categories of repetition to consider for ‘automatic’ processing using a concordancer program in order to produce summaries based on clusters of lexical repetition sequences, thus obtaining an outline of a text’s structure. The study’s findings are extended to the analysis of parallel texts: two professional translations of corpus text 1 are examined using the same procedure.